Determinant of Earnings Management Pre and Post PSAK 109 in Indonesian Banks - Wirza Aufa; Raudhatul Hidayah; Fitriyeni Oktavia (Jurnal Informatika Ekonomi Bisnis, 2024)
This study aims to determine the differences in Earnings Management and the effect of Institutional Ownership, Managerial Ownership, Audit Committee Competencies, Capital Adequacy Ratio (CAR), and Nonperforming Loan (NPL) on Earnings Management proxied by Discretionary Loan Loss Provision (DLLP) pre and post-PSAK 109 implementation in Indonesian bank listed on the Indonesian Stock Exchange (IDX). This study uses Ordinary Least Square (OLS) regression and Wilcoxon signed-rank test to test the hypothesis. The study used the period pre and post implementation of PSAK 109. We traced each bank's financial report listed on the IDX from 2017 to 2020 to anticipate early implementation. Using purposive sampling, we obtained 40 pre-PSAK 109 and 40 post-PSAK 109 bank samples. This study found no difference in earnings management pre and post-PSAK 109. Institutional Ownership, Managerial Ownership, and Audit Committee Competencies do not affect Earnings Management pre and post-PSAK 109. NPL is positively related to Earnings Management pre and post-PSAK 109, and CAR is positively related to Earnings Management pre-PSAK 109 but has no effect on Earnings Management post-PSAK 109. This study provides additional information for standard setters and OJK regarding monitoring earnings management practices in banking pre and post-PSAK 109.